2020
DOI: 10.1126/sciadv.abc8482
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation on “phagocytic synapse” arrays: Spacing of nanoclustered ligands directs TLR1/2 signaling with an intrinsic limit

Abstract: The activation of Toll-like receptor heterodimer 1/2 (TLR1/2) by microbial components plays a critical role in host immune responses against pathogens. TLR1/2 signaling is sensitive to the chemical structure of ligands, but its dependence on the spatial distribution of ligands on microbial surfaces remains unexplored. Here, we reveal the quantitative relationship between TLR1/2-triggered immune responses and the spacing of ligand clusters by designing an artificial “phagocytic synapse” nanoarray platform to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Lipopolysaccharide (LPS) molecules that contain different shapes of the lipid A component were also shown to activate different TLR heterodimers and subsequently different responses in mononuclear cells 54 , 55 . We have demonstrated here, and in our previous study, that the nanoscale proximity between receptors functions as another key regulatory mechanism for innate receptor crosstalk 24 , 56 . In addition to revealing a new role for spatial proximity in receptor crosstalk, our studies have also demonstrated that the geometric manipulation strategy we have established is more generally applicable for investigating the relationship between receptor crosstalk and the spatial organization of receptors on phagosome membranes in living cells.…”
Section: Discussionsupporting
confidence: 71%
“…Lipopolysaccharide (LPS) molecules that contain different shapes of the lipid A component were also shown to activate different TLR heterodimers and subsequently different responses in mononuclear cells 54 , 55 . We have demonstrated here, and in our previous study, that the nanoscale proximity between receptors functions as another key regulatory mechanism for innate receptor crosstalk 24 , 56 . In addition to revealing a new role for spatial proximity in receptor crosstalk, our studies have also demonstrated that the geometric manipulation strategy we have established is more generally applicable for investigating the relationship between receptor crosstalk and the spatial organization of receptors on phagosome membranes in living cells.…”
Section: Discussionsupporting
confidence: 71%
“…Compared to the SBM group, the decreased number of both neutrophils and macrophages may result from the significantly restrained tnf-α expression. For macrophages, fewer immune synapse-like structures in the SN group may suggest the inhibition of innate immune cells’ migration and phagocytic activity ( 67 , 68 ), and the inhibition of the M1 phase at the mucosa ( 60 ). These results of fish macrophages were in line with the findings in mammals that the interaction with α7nAChR expressed on macrophages leads to a reduction of pro-inflammatory cytokines ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the TLR2-TLR1 clusters are adjacent to one another, the immune responses reach the maximum. The nanoclusters do not coalesce into larger ones, even with excess density of ligands (Li et al, 2020a). This study thus provides quantitative and direct evidence that the proximity of TLR2-TLR1 nanoclusters modulates immune responses in macrophages.…”
Section: Nanotechnology-based Methods For Investigating Innate Receptor Clustersmentioning
confidence: 63%
“…Compared to micropatterned substrates, nanoscale patterning of ligands is technically more challenging. Recently, we created nanopatterned arrays of Pam 3 CSK 4 (a ligand for the TLR1-TLR2 heterodimer) to investigate how the spacing of TLR2-TLR1 receptor nanoclusters regulates macrophage activation (Li et al, 2020a) (Fig. 3B).…”
Section: Nanotechnology-based Methods For Investigating Innate Receptor Clustersmentioning
confidence: 99%